Efeitos do tamoxifeno e do anastrozol na periodontite induzida por ligadura em ratas ovariectomizadas - Melo, Iracema Matos de (2017)
Tamoxifen (TMX) and anastrozole (ANA) are selective estrogen receptor modulators and aromatase inhibitors drugs, respectively, used in the therapy of breast cancer, impacting on the bone tissue. The effect of TMX and ANA on the ligature-induced periodontitis in ovariectomized (OVX) rats was evaluated. Initially, 170 Wistar rats were sham-ovariectomized (S-OVX) or OVX. On day seven, periodontitis was induced by ligature (nylon 3.0) on the upper left second molar and the contralateral one as control. Groups of animals received through gavage distilled water (Normal, S-OVX, and OVX), TMX (OVX/TMX 1, 3, and 9 mg/kg) or ANA (S-OVX/ANA 0.5 or OVX/ANA 0.02, 0.1, and 0.5 mg/kg), daily, for 28 days, when were subjected to euthanasia. The gingiva was analyzed through dosages of myeloperoxidase activity (MPO) and TNF-α by ELISA, and the alveolar bone resorption (ABR) was assessed by macroscopic, histometric, histological, and immunohistochemical analysis for TNF-α, RANKL, OPG, and TRAP. Systemically, the following parameters were analyzed: the femur by histological analysis, estradiol serum dosages (ESD), total alkaline phosphatase (TALP) and bone alkaline phosphatase (BALP), the leukogram, the uterus wet weight (UWW), and body mass variation (BMV). The OVX caused hypoestrogenism in relation to basal values and S-OVX animals; without altering by TMX, but reduced by ANA. The UWW was reduced in OVX, OVX/TMX, OVX/ANA and in the S-OVX/ANA animals in relation to normal and S-OVX animals. The second molar ligature caused ABR (macroscopic and microscopies), increase in the gingival levels of MPO and TNF-α, in the immunolabelling for RANKL, ratio RANKL/OPG and TRAP, and reduction of OPG and BALP. The hypoestrogenism due to OVX increased only MPO in relation to the S-OVX. TMX reduced the ABR, besides the MPO, the immunolabelling for TNF-α, RANKL, and TRAP, with a lower ratio of RANKL/OPG, and increased the BALP levels, maintaining the OPG levels close to the normal group values. ANA in S-VOX animals did not altered the evaluated parameters. However, when combined with OVX, the additional hypoestrogenism seen in the OVX/ANA group, albeit it did not increase the MPO and TNF-α in relation to what was observed in non-treated OVX animals, it did increase the ABR associated with the increase in the MPO in relation to S-OVX animals as well as the rise in the RANKL, RANKL/OPG ratio, and TRAP, and it reduced both OPG and BALP. The femoral analysis showed that the OVX did not promote significant bone alterations in comparison with the Normal and S-OVX groups, as well as compared with TMX-treated animals. ANA promoted changes in the femur of S-OVX and OVX animals, with presence of fibrous connective tissue in the epiphysis, inflammation in the periosteum and broad spinal spaces, especially in OVX animals. The periodontitis induced leukocytosis at the expenses of neutrophilia and lymphomonocytosis, and added to OVX observed a leukocytosis increasing. This was prevented by TMX and did not alter by ANA. Finally, the OVX promoted a higher weight gain in relation to the Normal and S-OVX animals. OVX/TMX resulted in lower weight gain, and OVX/ANA, curve similar to that of OVX. In summary, the modulation of estrogen receptors by TMX prevented the bone resorption due to a reduction in the inflammatory response and potentially favoring the bone formation via the modulation of osteoclastogenic cytokines, while the estrogen synthesis inhibition by ANA, besides increasing bone destruction, it even reduced the mechanisms of bone formation.